Casting vs Surgical Treatment of Children With Medial Epicondyle Fractures - Grahn, Petra; Helenius, Ilkka; Hämäläinen, Tero; Kivisaari, Reetta; Nietosvaara, Yrjänä; Sinikumpu, Juha-Jaakko; Jalkanen, Jenni; Löyttyniemi, Eliisa; Ahonen, Matti; Finnish Pediatric Orthopedic Study Group Investigators (American Medical Association (AMA), 2025)
Importance: Displaced pediatric medial humeral epicondyle fractures are traditionally treated nonoperatively with casting. However, the use of surgical treatment has increased despite limited high-level evidence supporting its benefits.
Objective: To determine whether open surgical reduction and internal fixation improve functional outcomes compared with long arm casting in children with displaced medial humeral epicondyle fractures at 12 months post injury.
Design, setting, and participants: This noninferiority randomized clinical trial was conducted in 4 university hospitals in Finland between August 30, 2019, and August 22, 2023, with a 12-month follow-up completed August 20, 2024. Participants included children (aged 7-16 years) with nonincarcerated medial humeral epicondyle fractures and more than 2 mm of displacement. Data analysis was based on intention to treat.
Interventions: Open reduction and fixation, followed by a long arm cast for 4 weeks, or long arm cast without reduction for 4 weeks.
Main outcome and measure: The primary outcome was the Quick Disabilities of the Arm, Shoulder, and Hand (QDASH) score at 12 months (range, 0-100 points, with 0 denoting no disability and 100 extreme disability; prespecified noninferiority margin was 6.8 points).
Results: Seventy-two patients were randomized (43 [59.7%] female; mean [SD] age, 12.1 [2.1] years; range, 7.9-15.9 years), with 37 (19 [51.4%] female) to the surgery group (mean [SD] age, 12.2 [2.3] years; range, 7.9-15.9 years) and 35 (24 [68.6%] female) to the cast group (mean [SD] age, 11.9 [2.0] years; range 7.9-15.9 years). At 12 months, the mean QDASH score was 1.73 (95% CI, 0.65-2.81) in the surgery group and 2.71 (95% CI, 0.52-4.90) in the cast group, showing noninferiority (mean difference, -0.98 [95% CI, -2.95 to 0.98] points). The cosmetic visual analog scale favored the cast group, with a statistically significant between-group difference of -8.9 points (95% CI, -16.6 to -1.2 points; P < .001). Nonunion occurred in 1 of 37 surgically treated patients (2.7%) and 24 of 35 cast-treated patients (68.6%). No crossovers from casting to surgery occurred.
Conclusions and relevance: In this randomized clinical trial of displaced medial epicondyle fractures, treatment with casting alone was noninferior at 12 months to surgical reduction and internal fixation followed by casting. Findings support nonoperative care as effective at 1 year; longer-term outcomes remain to be studied.
Trial RegistrationClinicalTrials.gov Identifier: NCT04531085